Ventriloquial Sensemaking of End-of-Life Care and Graduate Medical Education: A Case Study from Abu Dhabi - Ibrahim H; Harhara T; Dutta D (Taylor and Francis Group, 2025)
Previous research has emphasized the role of clinician-educators as providers of knowledge and expertise for medical trainees, centralizing the power of voice and agency in these interactions. Rhetoric of health and medicine encompass nuanced observations of health and medicine practices by foregrounding discourses contextualizing communication. These are particularly relevant for studying persuasive practices in health and medicine that identify challenging issues and decision-making by caregivers. In this case study from the United Arab Emirates, we argue through the lens of rhetorical ventriloquism that contextual factors play roles in shaping training discourses in physician-resident communication. Through analysis of 18 interviews, we found that when ambiguities prevail in the context of taken-for-granted training practices, cultural, social, and structural intersections emerge to stand in and shape the ways in which medical education around end-of-life care is constructed. Implications of the findings for the scholars, educators, trainers, and health practitioners are discussed.